Jumping acelerometric study of elite handball female athletes with or without previous anterior cruciate ligament reconstruction - Setuain, I.; Millor, N.; Gorostiaga, E.; Garcia, I.; Alfaro, J.; González Izal, M.; Izquierdo, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Measuring movement-pattern related variables during the rehabilitation process would help to identify possible movement patterns associated with a previous ACL reconstructed limb. PURPOSE: To Identify possible differences between previously ACL injured and uninjured athletes focusing on jumping performance and 3 orthogonal axis kinematic variables among a group of 20 female handball elite athletes in the vertical unilateral drop jump (VBDJ) task. METHODS: A cross- sectional descriptive study was carried out in order to analyze jumping performance and movement pattern among 20 female elite handball players (6 previously injured and reconstructed and 14 uninjured subjects) during the execution of a VBDJ. An inertial orientation tracker MTx attached over the L3 region of the subject`s lumbar spine provided the kinetic data recorded in each trial at a sampling rate of 100 Hz. VBDJ was divided for biomechanical analysis into three phases (initial absorption phase; IA, drive phase, and final absorption phase; FA. RESULTS: Previously ACL reconstructed athletes displayed greater mediolateral, anteroposterior and vertical axis peak accelerations in the IA, DP and FA jumping phases but not in the z axis, where the FA was not different (p>0.05) (X axis IA 13,15 ± 6,26 vs 0,13 ± 11,93; DP 2,70 ± 1,10 vs -0,48 ± 3,55; FA 8,58 ± 6,06 vs -0,71 ± 11,47; Y axis IA 14,66 ± 7,48 vs -6,17 ± 22,61; DP 6,27 ± 1,92 vs -4,90 ± 13,47; FA 9,30 ± 3,22 vs -9,43 ± 18,82; Z axis IA 49,86 ± 8,45 vs 39,84 ± 11,1; DF 16,68 ± 6,16 vs 12,39 ± 5,75 m•s-2).Significant relationships were found between Z axis peak acceleration in the IA phase and flight time (r =0. 38; P<0.05)), DP Z axis peak acceleration and drive phase time duration (r = -0,50) and Z axis peak acceleration in the IA and IA phase duration ( r = 0,48) among the control athletes. In contrast only the correlation between IA Z axis peak acceleration and IA time phase (r = -0.68) time resulted significant among previously ACL reconstructed group. CONCLUSION: Previously ACL reconstructed athletes showed significantly different movement patterns during the execution of the VBDJ comparison to non ACL injured controls. It may suggests that some different supporting forces distribution strategies in comparison with non ACL reconstructed control players could persist among previously ACL reconstructed elite female handball players despite having return to elite competition .Furthermore, the fact that more significant correlations were found among non ACL reconstructed athletes could indicate a more reproducible movement pattern among this group.